2004
DOI: 10.1111/j.1440-1797.2003.00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal imaging in pyelonephritis

Abstract: Although our study did not test whether immediate imaging is more advantageous than delaying imaging for those who fail to respond to treatment, our findings suggest that early imaging is a cost-effective part of management. On the basis of these data, we recommend renal imaging for all patients requiring hospital admission for pyelonephritis, and suggest that initial empirical therapy should include an intravenous dose of cephalosporin but not ampicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
2
11
0
1
Order By: Relevance
“…In this journal, 16% of patients were found to have new and clinically significant abnormal findings. But there was no significant difference between the groups with abnormal renal imaging and those with normal renal imaging in terms of any easily detectable clinical parameter, such as change in serum creatinine, premorbid conditions, age, days for fever to resolve, or white cell count on admission [6]. This finding suggests that early imaging is a cost-effective part of management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this journal, 16% of patients were found to have new and clinically significant abnormal findings. But there was no significant difference between the groups with abnormal renal imaging and those with normal renal imaging in terms of any easily detectable clinical parameter, such as change in serum creatinine, premorbid conditions, age, days for fever to resolve, or white cell count on admission [6]. This finding suggests that early imaging is a cost-effective part of management.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, making an exact clinical correlation with the various stages of inflammation that cause abscess, calculi, or obstruction, all of which require immediate intervention or an appropriate surgical procedure, is impossible [4]. In this context, recent studies have emphasized the importance of early imaging [5,6]. Improving prognosis by identifying abnormalities, such as complications, that cannot be detected by clinical findings or laboratory findings is important.…”
Section: Introductionmentioning
confidence: 99%
“…I nostri dati preliminari confermano osservazioni già fatte in precedenza 9 . È importante notare che in alcuni casi sono assenti alcuni dei sintomi considerati tra i più suggestivi di pielonefrite acuta: in particolare, 2 pazienti con infezione alta e danno renale dimostrato, non avevano dolore lombare, che, al contrario, era presente in tutte le pazienti non affette da pielonefrite acuta.…”
Section: Discussioneunclassified
“…Recent reports imply the importance of early imaging. Shen and Brown stated that early imaging is cost-effective and advocate imaging in people who are going to be hospitalized by APN (14,15). Yoo et al (14) reported that there are clinically significant findings in 16% of the patients.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%